PENGARUH DER, EPS, DAN ROA TERHADAP HARGA SAHAM PERUSAHAAN FARMASI DI BEI PERIODE 2020-2023 - Windy Nur Octaviana; Umi Nadhiroh; Nurali Agus Najibul Zamzam (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
Analyzing the effect of DER (Debt Equity Ratio), EPS (Earning per Share) and ROA (Return On Asset)s on stock prices is the purpose of this study. The study involved is all pharmaceutical companies listed on the IDX as a population and produces 11 companies as a population which are then selected through purposive sampling techniques and produce 9 pharmaceutical companies. Regression data panel uses E-views 9 software as its analysis method. The research findings show that there is no partial effect between DER and the stock prices of pharmaceutical companies listed on the IDX in 2020-2023. There is a partial effect between ROA and EPS on the stock prices of pharmaceutical companies listed on the IDX in 2020-2023, and there is a simultaneous effect between DER, EPS and ROA on the stock prices of pharmaceutical companies listed on the IDX in 2020-2023. Thus, it is necessary to pay more attention to the financial performance of EPS and ROA aspects, which can provide positive signals for investors and affect the stock price.